When we <em>divide </em>both sides of the <em>inequality</em>,
3x > 27 by 3, <em>3x(3) > 27(3)</em>
we get x > 9, as the <em>simplified form </em>of the<em> inequality.</em>
Thus, giving us the answer of:
<em>x > 9</em>
Answer:
see below
Step-by-step explanation:
sin x 1
------------------- = -----------
sec^2 x - tan ^2 x csc x
Sec = 1/cos and tan = sin/cos
sin x 1
------------------- = -----------
1/ cos ^2 x -sin^2/cos ^2 x csc x
Factor the denominator
sin x 1
------------------- = -----------
(1-sin^2 x)/ cos ^2 x csc x
We know that 1 - sin^2 x = cos ^2
sin x 1
------------------- = -----------
(cos^2 x)/ cos ^2 x csc x
sin x 1
------------------- = -----------
1 csc x
Multiply the top and bottom of the left hand side by 1/ sin x
sin x * 1/ sin x 1
------------------- = -----------
1 * 1 sin x csc x
1 1
------------------- = -----------
1 sin x csc x
We know that 1/sin x = csc
1 1
--------- = -----------
csc (x) csc x
Multiplying binomial and polynomials can be easy as long as you follow the steps for example:
Let's say you were multiplying 3x-3 and x+2
(3x-3)(x+2)
remember FOIL
OR think about it like this(see attatchment)
3x^2 + 3x -6 is what you should get
Answer:
16.2
Step-by-step explanation:
4*2.8+5=